Kemajuan Belajar Siswa pada Penjumlahan Bilangan Desimal Menggunakan Pengukuran Berat - Maimuna, Leni; Darmawijoyo, Darmawijoyo; Susanti, Ely (UIN Sunan Ampel Surabaya, 2018)
This study was aimed at describing the studentâ learning progress on decimals addition by a set of learning activitis based on Indonesian Realistic Mathematics Education. This research  method is design research which contain three stages, namely: preliminary design, design experiment and retrospective analysis. Hypothetical Learning Trajectory (HLT) has been designed to play an important role as learning design and research instrument. HLT was tested to 30 fourth grade students. The data were collected through interview, observation, and field notes. The findings of the research  showed that this instructional design could stimulate students  in the introduction of one digit decimal through the result of weight measurement, the use of the model that the students make themselves (model of) to describe the measurement results at the second level, and marking the result of the measurement to the number line and continued by describing the process of decimals addition from the measurement activity to the number line in the more formal level. Furthermore at the formal level, students are able to solve the problem of the decimals addition using the correct procedure that is the place value rule.